Urban Conservation as a Development Strategy to Revitalize Real Estate Market: An Analysis of Property Transactions in Georgetown Penang - Yusof, Nor'Aini; Lim, Yoke Mui; Lee, Lik Meng (Penerbit Universiti Sains Malaysia, 2007)
Penang is well known for its heritage character especially in the city of Georgetown with more than 200 years of urban history. To retain its heritage character, the state and local governments have implemented various conservation policies and identified a heritage zone in the inner city of Georgetown. In many parts of the world, designation as a heritage property would have increased a property's value and this is one of the reasons put forward for urban conservation in Georgetown but so far no analysis have been presented to support this claim. We developed an all-encompassing model to evaluate the effects of conservation related policies on the heritage property market. In this paper, we focus the analysis on data from property transactions and price to analyse and identify property trends in Georgetown from the year 1974 to 2004. The analysis is presented within the framework of public policy and intervention strategies, socio-economic and political changes. Our analysis of the transaction data and price trends shows that urban conservation has a potential to be a viable real estate development strategy for Georgetown. Even with conservation policies in place, the demand for old buildings in the conservation zones has not diminished but has shown relatively high transaction counts and high price of heritage properties.